2013
DOI: 10.1002/app.40215
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels containing silver nanoparticles for burn wounds show antimicrobial activity without cytotoxicity

Abstract: This research introduces a novel dressing for burn wounds, containing silver nanoparticles in hydrogels for infected burn care. The 2-acrylamido-2-methylpropane sulfonic acid sodium salt hydrogels containing silver nanoparticles have been prepared via ultraviolet radiation. The formation of silver nanoparticles was monitored by surface plasmon bands and transmission electron microscopy. The concentration of silver nitrate loaded in the solutions slightly affected the physical properties and mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Also, rosemary essential oils loaded-chitosan benzoic acid nanogel had an antimicrobial effect against S. aureus (Mohsenabadi et al, 2018) as the same result of gentamycin sulfate loaded chitosan nanogel (Wu et al, 2014) and vancomycin loaded mannose hydrogel that had anti-MRSA effect (Xiong et al, 2012). Silver nanoparticles loaded (poly-N-Iso-propyl acrylamide nanogel (Qasim et al, 2018), polyacrylic acid (Choi et al, 2013), Alginate nanocomposite hydrogel (Stojkovska et al, 2014), Acrylamide-methylpropane hydrogel (Boonkaew et al, 2014), and Fumaric acid cross linked-carboxy methyl acetate hydrogel (Bozaci et al, 2015) exhibited a potent bactericidal effect against S. aureus infection.…”
Section: Nanogelsmentioning
confidence: 87%
“…Also, rosemary essential oils loaded-chitosan benzoic acid nanogel had an antimicrobial effect against S. aureus (Mohsenabadi et al, 2018) as the same result of gentamycin sulfate loaded chitosan nanogel (Wu et al, 2014) and vancomycin loaded mannose hydrogel that had anti-MRSA effect (Xiong et al, 2012). Silver nanoparticles loaded (poly-N-Iso-propyl acrylamide nanogel (Qasim et al, 2018), polyacrylic acid (Choi et al, 2013), Alginate nanocomposite hydrogel (Stojkovska et al, 2014), Acrylamide-methylpropane hydrogel (Boonkaew et al, 2014), and Fumaric acid cross linked-carboxy methyl acetate hydrogel (Bozaci et al, 2015) exhibited a potent bactericidal effect against S. aureus infection.…”
Section: Nanogelsmentioning
confidence: 87%
“…Hydrogels of 2-acrylamido-2-methylpropane sulfonic acid sodium salt containing Ag NPs have been proved to have no cytotoxicity while exhibiting better antimicrobial ability than commercial Acticoatℱ (Smith & Nephew, London, UK) and PolyMem Silver Âź (Ferris Mfg. Corp., Fort Worth, TX, US), 66,67 which can give us more confidence in exploitation of Ag NP hydrogels. However, some researchers would like to try some new International Journal of Nanomedicine 2018:13 submit your manuscript | www.dovepress.com…”
Section: Sliver Nanoparticles (Ag Nps)mentioning
confidence: 99%
“…Studies have shown that the cytotoxic effects of silver are highly dependent on silver particle size, dose and exposure time . To better understand the reduced cytotoxicity of the silver‐CaP loaded composite, we performed a silver ion release study.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been shown that for polylactic acid (PLA) loaded with 1% silver particles, the proliferation rate of human skin cells cultured on the scaffolds is significantly reduced . It is believed that the cytotoxicity associated with silver particles is highly dependent on the size, concentration and release profile of silver from the material . With a higher silver loading content, a significant decrease in cell viability or proliferation rate is often observed …”
Section: Introductionmentioning
confidence: 99%